Retinopathy in a patient with systemic lupus erythematosus - Ildefonso Chan, MD; Franz Marie Cruz, MD; Cherica Tee, MD; Carien Gulay, MD; Leonila Dans, MD; Jennifer Otadoy-Agustin, MD; Marysia Recto, MD (Philippine Journal of Ophthalmology)
Objective: To descibe a case of bilateral severe ischemic retinopathy in a patient with systemic lupus erythematosus (SLE) and elevated antiphospholipid antibody.